The Prognostic Value of the DNA Repair Gene Signature in Head and Neck Squamous Cell Carcinoma - Ming, Ruijie; Wang, Enhao; Wei, Jiahui; Shen, Jinxiong; Zong, Shimin; Xiao, Hongjun (Frontiers in Oncology, 2021)
Purpose: This study aims to construct a prognostic signature composed of DNA repair genes to effectively predict the clinical outcome prognosis of patients with head and neck squamous cell carcinoma (HNSCC). Methods: In this study, after downloading the transcriptome and clinical data of HNSCC from TCGA, the HNSCC patients were equally divided into the training set and the testing set. In the training set, 13 DNA repair genes were screened out through univariate proportional hazard (Cox) regression analysis and Lasso Cox regression analysis to construct a risk model, and then the model was validated in the testing set. Results: In the training set and testing set, there were significant differences in the clinical outcomes of patients in the high- and low-risk groups. Univariate and multivariate Cox regression analysis showed that the risk score had the independent prognostic predictive ability. At the same time, the immune cell infiltration, immune score, immune-related gene expression, and tumor mutation burden of patients with HNSCC were also different between the high- and low-risk groups. Finally, we screened several chemotherapeutics for HNSCC that had significant differences in drug sensitivity in the high- and low-risk groups. Conclusion: We assumed that the model constructed by DNA repair genes in this study could effectively predict the clinical outcome of patients with HNSCC.